2000
DOI: 10.1016/s1074-7613(00)80179-x
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Mechanism for the Induction of Cytotoxic T Lymphocyte Production by Heat Shock Fusion Proteins

Abstract: A 65 kDa mycobacterial heat shock protein (hsp65), fused to a polypeptide that contains an octapeptide (SIYRYYGL) agonist for a particular T cell receptor (2C TCR), stimulated C57BL/6 mice as well as CD4-deficient mice to produce CD8+ cytolytic T lymphocytes (CTL) to the fusion partner's octapeptide. This and other hsp65 fusion proteins but not native hsp65 itself stimulated dendritic cells in vitro and in vivo to upregulate the levels of MHC (class I and II) and costimulatory (B7.2) molecules. The results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
2

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 39 publications
3
87
0
2
Order By: Relevance
“…7). These results are consistent with previous reports showing that HSP fusion proteins can induce potent immune responses both in mice and humans [24][25][26], further validating the general approach of using HSP fusion proteins in inducing anti-tumor responses.…”
Section: Discussionsupporting
confidence: 92%
“…7). These results are consistent with previous reports showing that HSP fusion proteins can induce potent immune responses both in mice and humans [24][25][26], further validating the general approach of using HSP fusion proteins in inducing anti-tumor responses.…”
Section: Discussionsupporting
confidence: 92%
“…Briefly, the Ag cassette containing the SIY-peptide, a sequence previously shown to induce strong anti-SIY responses (28), was introduced into the bacterial genome by homologous recombination as previously described (29). Mice were infected by i.v.…”
Section: Recombinant Lm (Rlm)-siy and Infectionmentioning
confidence: 99%
“…However, among EBV latent-cycle proteins, CD4 + T responses to LMP2A epitopes are much less frequent than EBNA1 and LMP1 (18). Previous studies have demonstrated that MtHsp70 accompanied antigens can induce potential antigen-specific CD8 + T cells with cytolytic and cytokine-secreting functions through CD4 + T cell independent modes (21,23,(39)(40)(41)(42). In this study, we conjugated a conserved LMP2A HLA-A2.1 restricted epitope LMP2A 356-364 to MtHsp70, which not only induces LMP2A 356-364 specific immune recognition in vitro, but also elicits LMP2A specific CTL in vivo.…”
Section: Discussionmentioning
confidence: 99%